Effect of Different Alternative Growth Promoters on Development of Antibody Against Newcastle Disease Virus and Serum Trace Minerals in Khaki Campbell Ducks - Lalhriatpuii, Melody; Samanta, Goutam; Patra, Amlan Kumar; Pal, Koushik (Indian Journal of Animal Nutrition, 2018)
An experiment was conducted to evaluate the effect of different dietary growth promoters on development of antibody against Newcastle disease virus and serum trace minerals in Khaki Campbell ducks. A total of three hundred twenty ducklings were distributed randomly into one control and seven treatmentgroups. The control group was fed maize grains and soybean meal based basal diet while seven treatment groups were supplemented with organic acids combination (ammonium formate, calcium propionate, calcium lactate) @ 0.1% each, yeast nucleotides @ 2%, bacteriophage @ 250 g/tonne of feed, antibiotic powder (Kitacin) @ 100 g/tonne of feed, bacteriophage and yeast extract @ 100 g/tonne of feed, sodium butyrate @ 300 g/tonne of feed and ethyl butyrate @ 2.5 ml/liter of water along with the basal diet. The feed samples were analyzed for detection of fungi and microbes. The ducks were vaccinated against Newcastle disease (live B1 at d 7 and Lasota at d 21). Serum trace mineral concentrations iron (Fe), manganese (Mn) and Zinc (Zn) were analyzed to find out the effect of different feed additives. Total viable counts of fungi in treatment groups were lower (P